EVALUATION OF THE PHYSICAL AND CHEMICAL PROPERTIES OF BIO-CHAR DERIVED FROM THE PYROLYSIS OF MORINGA OLEIFERA SEEDS - Muhammad Ziddun Ni’am; Wahyudi; Fitriyana, Deni Fajar; Sonika Maulana; Sukarni; Samsudin Anis (Jurnal Bahan Alam Terbarukan, 2025)
This study aims to assess the potential of bio-char derived from Moringa oleifera seeds through an evaluation of its physical and chemical properties. Moringa oleifera seeds were processed into fine powder, dried, and then subjected to pyrolysis at 400°C using a microwave reactor. Nitrogen gas was introduced before and during the pyrolysis process to create a low-oxygen environment. The pyrolysis continued until no more condensable vapors were detected, indicating that the thermal decomposition process had reached completion. The resulting bio-char was collected and analyzed to determine its physical and chemical characteristics, including proximate analysis (moisture content, ash content, volatile matter, and fixed carbon), calorific value, and density. The results showed that the bio-char from Moringa oleifera seed powder had a very high fixed carbon content of 79.13% and low volatile matter. The calorific value reached 25.04 MJ/kg, which is comparable to that of low-rank coal. Additionally, the bio-char had a density of 0.905 g/cm³, which is relatively high compared to most biomass-derived bio-chars. These characteristics indicate that bio-char from Moringa oleifera seeds holds significant potential for use as a solid fuel in the form of briquettes or pellets, as a biomass energy source, and as a long-term carbon storage medium for climate change mitigation.